Examining Indonesian Government Strategies in the Aviation Sector Post Covid-19 Pandemic - Hanna Khairunnisa Adjie; Diana Mutiara Bahari (Journal of Contemporary Governance and Public Policy, 2021)
Aviation is an inseparable part of transportation in any country. The aviation sector is one of the sectors most affected by the Covid-19 pandemic. Indirectly, the spread of the Covid-19 virus can occur in airlines, which are the fast transportation options for passengers. Indonesia has taken a policy to stop its aviation sector from reducing the spread of the Covid-19 virus and prioritize the health of its citizens. The drastically reduced flight frequency without clarity of time impacts many losses to the aviation industry. The Indonesian government plans a gradual recovery effort in the aviation sector through domestic flights. However, there are concerns from the Indonesian people, as airline passengers who will be traveling, regarding their health safety on flights during the large-scale social distancing period during the Covid-19 pandemic. Therefore, this study will discuss the strategies of the Indonesian government in the aviation sector after the Covid-19 pandemic to still prioritize the health of its citizens. This study uses the theory of the foreign policy decision-making process. The method used in this study is a qualitative based research method. This study concludes that the strategies taken by the Indonesian government include reducing 50% of passenger capacity to enforce safe distances, sanitizing aircraft, and for prospective passengers to be required to show a certificate of negative Covid-19 results through a PCR swab test or GeNose C19.